EARLY FUNCTIONAL RECOVERY AFTER LAPAROSCOPIC SURGERY FOLLOWING NEOADJUVANT CHEMOTHERAPY IN STAGE III GASTRIC CANCER (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Surgery remains the cornerstone of curative treatment for locally advanced gastric cancer. In stage III disease, surgical treatment is often combined with neoadjuvant chemotherapy. However, surgery after neoadjuvant treatment may be technically more demanding, and the role of laparoscopic surgery in this setting remains clinically relevant.Objective: To evaluate early functional recovery and short-term surgical outcomes after laparoscopic gastrectomy following neoadjuvant chemotherapy in patients with stage III gastric cancer.
Keywords: Gastric cancer, stage III, laparoscopic gastrectomy, neoadjuvant chemotherapy, functional recovery, hospital stay, postoperative pain.